Recepcija treh kratkih zgodb med bralci z različnih ravni šolanja - Pezdirc-Bartol, Mateja (Slavistična revija, 2002)
In reading a text, our comprehension is determined by a least two factors: on the one hand there is the text, which relates particular knowledge and direct our understanding with its structure and textual codes; on the other there is the reader, who is not a neutral, passive receiver, but is socially and historically defined, while his reading is also directed by his individual, specific characteristics. The purpose of the study was to find the differences and similarities in the reception on three stories between readers with various levels of education and with various literary knowledge, i.e., in their attitude and motivation for reading, literary interests, appeal of the stories, evaluative opinions, and understanding and interpretation.
Keywords: Blatnik, Andrej, 1963-; branje; Kleč, Milan, 1954-; kratka proza; literarna percepcija; pouk književnosti; Slovene literature; slovenska književnost; Šušulić, Aleksa, 1961-